Assessing the impact of Social Innovation Education on student’s engagement. European Journal Of Sustainable Development - Kalemaki, Irene; Garefi, Ioana; Protopsaltis, Aristidis (European Journal of Sustainable Development, 2021)
This paper presents the findings of the H2020 NEMESIS project that aims to design, test and validate a consolidated approach for embedding Social Innovation in Education. Social Innovation Education (SIE) is a new educational approach that aims to empower students to take action for a more democratic and sustainable society. During the academic year 2018-2019, eight schools from five European countries applied the NEMESIS SIE framework by involving 56 teachers, 1030 students and 69 community members in a variety of SIE approaches. This paper reports on these attempts with a particular focus on analyzing their impact on student's engagement. Data were retrieved through focus groups with 80 people, an online survey to 206 students, interviews, classroom observations and students' narratives. Research findings suggested positive outcomes for students in terms of emotional, cognitive, behavioral and agentic engagement. Findings also showed a positive influence of SIE on the cultivation and progression of student s' social innovation competences. These initial findings have the potential to pave the way for more research in the under investigated field of SIE as well as to encourage policies and initiatives for promoting social innovation in education This paper presents the findings of the H2020 NEMESIS project that aims to design, test and validate a consolidated approach for embedding Social Innovation in Education. Social Innovation Education (SIE) is a new educational approach that aims to empower students to take action for a more democratic and sustainable society. During the academic year 2018 - 2019, eight schools from five European countries applied the NEMESIS SIE framework by involving 56 teachers, 1030 students and 69 community members in a va riety of YOU approaches. This paper reports on these attempts with a particular focus on analyzing their impact on student's engagement. Data were retrieved through focus groups with 80 people, an online survey to 206 students, interviews, classroom observ ations and students' narratives. Research findings suggested positive outcomes for students in terms of emotional, cognitive, behavioral and agentic engagement. Findings also showed a positive influence of SIE on the cultivation and progression of student s' social innovation competences. These initial findings have the potential to pave the way for more research in the under investigated field of SIE as well as to encourage policies and initiatives for promoting social innovation in education
Keywords: Social Innovation; Education; impact; cognitive; behavioural; emotional; agentic engagement